Exotic tick detected in Argentina on a tourist returning from South Africa - Tarragona, Evelina Luisa (2021)
The aim of this study was to report the finding of a nymph attached to an Argentinean tourist returning from South Africa. The nymph specimen was morphologically analysed, submitted to DNA extraction and amplifying the 16S rRNA mitochondrial gene. Additionally, the nymph DNA was screened for Rickettsia, Ehrlichia and Anaplasma infection. The nymph was determined to belong to Amblyomma marmoreum species complex. No specific diagnosis was achieved because the comparative descriptions of species in this complex contain important discordances, and the DNA sequence obtained in the present study is positioned within the same clade with sequences of A. marmoreum see above, but the genetic divergence with them (4.96 and 5.76%) indicate that they belong to different species. No DNA of the Rickettsiales order bacterial was detected in the A. marmoreum species complex nymph.